Landslide dam in river bed of Leva reka near Kraljevo due to cyclone ,,Tamara' in May 2014 - Jevremović Dragutin D.; Kostić Srđan D.; Andrejev Katarina D. (Tehnika, 2015)
In this professional paper authors present engineering-geological conditions of landslide activation at the right bank of Leva reka, in the basin of Velika reka, which flows into West Morava near Kraljevo, as its left tributary. Immediate cause of landslide activation is intense rainfall during the May in 2014. Results of the detailed engineering-geological field mapping of the area endangered by sliding indicate that landslide was formed within the Cretaceous flysch formation with predominant fraction of clay stones and marlstones, which show unfavorable engineering-geological properties. According to the most frequently used classifications, the observed landslide belongs to the group of fast, primary, consequent and detrusive landslides, and it was formed as an earthflow in weakly coherent materials. Landslide was formed in the lowest part of the slope, with deep sliding surface (approximately 10-12m below the surface), large area (over 10000m2) and volume (over 100 000m3). Based on the results of preliminary engineering-geological research, authors suggest following preventive remediation measures: regulation of Leva reka river bed throughout the accumulated material, controlled drainage of spring water at both sides of accumulated material directly into the river bed, including the leveling of the surface of landslide body.